Exploring digital literacy challenges and strategies among international students studying abroad - Anthonysamy, Lilian; Lim, Ooi Wei; Singh, Parmjit; Alasa, Victor (Journal of International Students, 2026)
This research explores how international students in Malaysian higher education develop digital literacy, the barriers that impede such development, and strategies that may enhance institutional support. To understand their experiences using digital tools within an academic context, semistructured interviews were conducted with international students in a qualitative design. The results showed that confidence develops through repeated use and structured support, and barriers include complexities of software applications, integration challenges across different platforms, and limited chances for hands-on training. Participants called for targeted workshops, peer mentorship, improved resource access, and early integration into the curriculum. This paper offers practical suggestions useful to universities seeking to foster international students’ adjustment to digitally mediated learning environments.